2006
DOI: 10.1159/000092598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hormone Replacement Therapy on Plasma Lipoproteins and Apolipoproteins, Endothelial Function and Myocardial Perfusion in Postmenopausal Women with Estrogen Receptor-α IVS1–397 C/C Genotype and Established Coronary Artery Disease

Abstract: Effect of hormone replacement (HRT) therapy on plasma lipoproteins and apolipoproteins, endothelial function and myocardial perfusion in postmenopausal women with estrogen receptor-α (ER-α) IVS1–397 C/C genotype and established coronary artery disease. Background/Aims: Associations between various ER-α polymorphisms and clinical phenotypes have been studied, including lipid levels and coronary atherosclerosis. We studied 48 postmenopausal women to determine the effect of ER-α IVS1–397 polymorphism on the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…However, Herrington et al (26) reported that postmenopausal women who were ESR1 PvuII CC carriers, as well as those with several other closely linked intron 1 polymorphisms, had an increase in HDL cholesterol levels after HRT. Later, these results were supported by the observation that postmenopausal women with an ESR1 PvuII CC genotype had an increase response of HDL, apolipoprotein A1, vascular reactivity, and myocardial perfusion to HRT (27). On the other hand, Huang et al (28) have reported that healthy postmenopausal women with the CC or TC genotype in ESR1 PvuII restriction had higher serum total cholesterol and LDL cholesterol concentrations.…”
Section: Introductionmentioning
confidence: 84%
“…However, Herrington et al (26) reported that postmenopausal women who were ESR1 PvuII CC carriers, as well as those with several other closely linked intron 1 polymorphisms, had an increase in HDL cholesterol levels after HRT. Later, these results were supported by the observation that postmenopausal women with an ESR1 PvuII CC genotype had an increase response of HDL, apolipoprotein A1, vascular reactivity, and myocardial perfusion to HRT (27). On the other hand, Huang et al (28) have reported that healthy postmenopausal women with the CC or TC genotype in ESR1 PvuII restriction had higher serum total cholesterol and LDL cholesterol concentrations.…”
Section: Introductionmentioning
confidence: 84%
“…phenotypes [20]. Post-MW with the ER IVS1-397 polymorphism C/C genotype (recessive) has more prominent increases in HDL and apolipoprotein A-1 levels compared to those with the dominant phenotype, as well as a greater degree of increased peak forearm blood flow, brachial artery diameter, and endothelium-dependent dilation [21]. In post-MW with established CAD and being treated with estrogen alone or estrogen plus progesterone, a two-fold greater increase in HDL levels was seen in women with the ER IVSI-401 polymorphism C/C genotype as compared to those without the polymorphism and undergoing the same treatment regimen [22].…”
Section: Vascular Estrogen Receptors (Ers)mentioning
confidence: 99%
“…As these receptors are also targeted by hormones administered exogenously, it is not surprising that these polymorphisms also influence the response to HT. Polymorphisms in the ER-α gene have been linked to more prominent increases in serum HDL:LDL cholesterol concentrations, improvements in endothelial function [44] and reductions in serum E selectin concentrations [45]. Polymorphisms in the progesterone receptor may similarly have an impact on the response to HT [46].…”
Section: Targeting the Appropriate Populationmentioning
confidence: 99%